2007
DOI: 10.4049/jimmunol.178.2.1077
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the MAPK, ERK, following Leishmania amazonensis Infection of Macrophages

Abstract: IL-10 is a critical cytokine in determining host susceptibility to Leishmania spp. We previously demonstrated that macrophage-derived IL-10 could contribute to disease exacerbation, but the mechanisms whereby Leishmania infections led to IL-10 induction were not fully understood. In this study, we demonstrated that infection of macrophages with Leishmania amazonensis amastigotes led to the activation of the MAPK, ERK1/2. This activation was required, but not sufficient for IL-10 induction. In addition to ERK a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
128
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(142 citation statements)
references
References 51 publications
12
128
2
Order By: Relevance
“…Of relevance to this study is the finding that lesion-derived La amastigotes can activate MAPK/ERK1/2 via the superinduction of IL-10 in MΦs (Yang et al, 2007), apparently through the prominent effects of FcγR signaling because these amastigotes are known to be coated with anti-Leishmania IgG Abs (Wanasen et al, 2008). In this study, we have provided strong evidence that alteration in DC signaling pathways during infection with Ab-free amastigotes is not due to endogenous IL-10.…”
Section: Discussionmentioning
confidence: 72%
“…Of relevance to this study is the finding that lesion-derived La amastigotes can activate MAPK/ERK1/2 via the superinduction of IL-10 in MΦs (Yang et al, 2007), apparently through the prominent effects of FcγR signaling because these amastigotes are known to be coated with anti-Leishmania IgG Abs (Wanasen et al, 2008). In this study, we have provided strong evidence that alteration in DC signaling pathways during infection with Ab-free amastigotes is not due to endogenous IL-10.…”
Section: Discussionmentioning
confidence: 72%
“…5) and human macrophages (13). However, we and others have shown that Erk1/2 MAPKs play a role in the regulation of IL-10 production in different model systems (58)(59)(60)62), such as following activation of macrophages with Leishmania amazonesis amastigotes (59,60). Likewise, dendritic cells from Erk 2/ 2 mice displayed a bias toward Th1 response manifested by enhanced IL-12p40 and reduced IL-10 production (58).…”
Section: Discussionmentioning
confidence: 99%
“…p38 MAPK regulates IL-10 production in both control and SHP-1-null splenic macrophages ERK has been shown to regulate IL-10 production in murine Th1 cells and macrophages (58)(59)(60)(61)(62). p38 MAPK also plays a critical ) were treated with PP2 (0.1-1 mM) for 2 h prior to LPS (10 mg/ml) stimulation for 24 h and IL-10 production was determined by ELISA.…”
Section: Restoration Of Shp-1 Expression In Me/me Splenic Macrophagesmentioning
confidence: 99%
“…This complex signaling pathway could either be activated or suppressed leading to the induction of gene products that favor parasite survival. While L. donovani inhibits EKR1/2, p38MAPK, and JNK activation in naïve macrophages leading to the suppression of pro-inflammatory cytokine production (Privé & Descoteaux, 2000), L. amazonensis activates ERK1/2 leading to the production of IL-10, a cytokine that contributes to parasite growth (Yang, Mosser, & Zhang, 2007). Mechanisms behind MAPK inactivation by Leishmania have been extensively studied.…”
Section: Mechanisms Of Immune Evasionmentioning
confidence: 99%